An overview of space situational awareness - Kennewell, J.; Vo, Ba-Ngu (IEEE, 2013)
Space Situational Awareness (SSA) means different things to different people, but in its broadest view refers to a knowledge of our near-space environment. This includes both a natural and man-made component. SSA is a term that has become prominent lately due to several collisions of orbiting space objects. This paper will briefly review the realm of SSA, the means by which we gather and process SSA, and the expected increase in a wide variety of SSA sensors that will result in large and diverse data streams that will require data fusion techniques and better data display methods to render more complete our knowledge and predictability of our immediate space environment.